Interaction of 3D parallel internal cracks in brittle solids under thermal loading: Experiment and numerical simulation - Wang, Yun-fei; Wang, Hai-jun; Zhao, Xin-ming; Tang, Lei; Pan, Jian-wu (Journal of Central South University, 2023)
Thermal fracture is a typical fracture. Cracks are widely present in brittle solids, and the stress concentration and propagation of cracks under temperature changes have an important effect on thermal fracture. Most of the traditional studies have focused on surface cracks or 2D cracks, while the propagation and the interaction of multiple internal cracks under temperature field are less frequently covered. This paper uses the 3D-internal laser-engraved crack (3D-ILC) method to fabricate 3D double-parallel internal cracks within intact cubic specimens, without causing any damage to the surface. Physical experiments and 3D numerical simulations of crack fracture in different vertical spacing under temperature fields are carried out, and the double crack interaction mode is analyzed and discussed. The results indicate the following: 1) When the double cracks are coplanar, then the temperature field distribution on both sides of the internal crack is symmetrical, the direction of double crack propagation does not shift, and the inner tips of the internal cracks attract each other and eventually coalesce. This is categorized as Mode I crack. In addition, coplanar crack propagation arcs intersect in an “I” shaped fracture morphology. 2) Double cracks attract and coalesce with each other when the ratio of vertical spacing d to crack radius a, i.e., d/a <2, and the interaction degree is maximum when d/a =1. Non-coplanar crack arcs are intersected by “crescent” shaped fracture morphology. 3) After d/a ⩾2, the propagation of the inner tip of the double crack is repulsive and this repulsion phenomenon is caused by the boundary effect, not the interaction between multiple cracks, thus categorizing them as Mode I–II mixed cracks. 4) Regardless of the size of the vertical spacing, the stress concentration phenomenon is present on both sides of the tip of the internal crack, while the inner side is much larger than the outer side, so the inner crack propagation length is longer than the outer side. The results of this study provide an experimental and theoretical basis for the study of three-dimensional double-parallel crack interactions under temperature fields.